Pengaruh Pengalaman Kerja ,Budaya Organisasi Dan Motivasi Kerja Terhadap Kinerja Pegawai Perhotelan Di Pondok Backpacker Hostel - Nur Kholis; Rois Arifin; Muhammad Ridwan Basalamah (E-JRM : Elektronik Jurnal Riset Manajemen, 2022)
Abstract This purpose of study : (1) to determine the effect of work experience on employee performance at the Backpacker Hostel. (2) to determine the effect of Organizational Culture on the Performance of Backpacker Hostel Employees (3) to determine the effect of Work Motivation on the Backpacker Hostel's Employee Performance (4) to determine the simultaneous effect of work experience, Organizational Culture and Work Motivation on the Backpacker Hostel's Employee Performance. In this study the population amounted to 35 respondents. Collecting data through distributing questionnaires using google form. Analysis of the data in this study using SPSS version 16. The technique of testing data with instrument testing uses a validity test, reliability test, and continued normality test, multiple linear regression analysis, and classical assumption test, multicollinearity test, heteroscedasticity test, testing research hypotheses. The results of the analysis show that: (1) There is a positive effect of the work experience variable on the Employee Performance variable at the Backpacker Hostel. (2) There is no positive effect of the Organizational Culture variable on the Employees Performance variable at the Backpacker Hostel. (3) There is a positive effect of the work motivation variable on the employee performance variable at the Backpacker Hostel. (4) There is a simultaneous positive effect of the variables of Work Experience, Organizational Culture and Work Motivation on the Variables of Employee Performance at Backpacker Hostel Keywords: Work Experience, Organizational Culture, Work Motivation and Employee Performance